Respuesta :

Answer:

[tex]a= \frac{9}{B+Q^2}[/tex]

Step-by-step explanation:

Given;

-Ba+9=Q²a

To solve for "a", make "a" the subject of the formula.

First, collect similar terms together;

-Ba - Q²a = -9

multiply through by "-1" to remove the negative sign;

Ba + Q²a = 9

factor out a;

a(B + Q²) = 9

divide both sides of the equation by "(B + Q²) ";

[tex]\frac{a(B+Q^2)}{B+Q^2} = \frac{9}{B+Q^2} \\\\a = \frac{9}{B+Q^2}[/tex]

Therefore, the value of "a" in the given expression is [tex]\frac{9}{B+Q^2}[/tex]